DESIGN AND DEVELOPMENT OF A NEW PORTABLE ROOF GUTTER FOR ELECTRICITY PRODUCTION - Hussein O.; Mustafa F.F.; Ghaeb N.H.; Sabry A.H. (Technology Center, 2023)
Despite a sufficient energy supply, harvesting energy from rainfall is essential for intelligent water management. A significant part is still untapped or little exploited, which is the renewable energy produced from rainwater. This paper proposes a portable gutter of the rainwater energy harvesting system to provide electricity that may be sufficient for powering lights and charging cell phones in rainy locations with limited electricity. A prototype is designed and tested to determine the feasibility of rainwater as a source of renewable energy. The aim is to minimize and respectively suspend the use of fossil energy sources, as well as decrease the percentage of pollution as it is a cause of global warming. The system prototype consisted of a gutter assembly that collected and funneled water from the roof to a downspout. The turbine was connected through a gearbox to a DC motor serving as the generator. The device is optimal during high rainfall intensities that produce larger flow rates. A smart algorithm has been applied, which is salutary to keep the system working and has the ability to control the flow of collected rainfall water. Also, this system is useful to install and use in the rural area where the national grids are not common and the level of rainfall is high. The applied system utilized and installed in more than one hundred premises can produce more than 4 kWh for one rain. In some countries such as Malaysia, the average number of rainy days is 250 days a year, so the use of this system in 100 premises can help to provide 80 MWh to the national grid yearly. The system is characterized by simplicity of design and lack of complexity in addition to ease of installation and cheapness, which is the basis for the availability of this system for use by everyone 2021, O. Hussein, Faiz. F. Mustafa, Nebras H. Ghaeb, Ahmed H. Sabry This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0)